Samoreprezentacije in identiteta zgodnjekrščanskih avtoric v prizmi starozaveznih likov - Bogataj, Jan Dominik (Bogoslovni vestnik, 2024)
The aim of this paper is to investigate the patterns of self-representation and the formation of their (female) identity in relation to Old Testament characters through a detailed study of all extant works by early Christian women authors (up to the beginning of the Middle Ages). The martyr Perpetua does this through an actualized reading of Genesis and Revelation (Eve-Mary). Proba and Eudocia re-tell the whole biblical history of redemption - with special attention and sympathy for the female perspective - through the verses of Virgil and Homer. Egeria, in her pilgrim’s diary, does not leave the Old Testament women (Lot’s wife, Rebecca, Sarah, Rachel) in the background, but gives them an equal role to men. In addition, some lesser-known texts by women authors are discussed. The study of these texts by early Christian women authors, precisely through this attention to the feminine aspect of self-representation and identity, shows the period of the first Christian centuries in a new light, while also shedding new light on the field of patristic (or 'matristic') exegesis.
Keywords: biblical exegesis; biblična eksegeza; Christian feminism; Christianity; early Christianity; feminism; feminizem; krščanski feminizem; krščanstvo; patristic exegesis; patristična eksegeza; women’s studies; zgodnje krščanstvo; ženske študije